2020
DOI: 10.51850/wrj.2020.11.1.27-34
|View full text |Cite
|
Sign up to set email alerts
|

Phenol Contents and Antioxidant Activity of Sonokeling (Dalbergia latifolia Roxb) Wood

Abstract: Dalbergia latifolia or sonokeling is a native species of Java, Indonesia, used as an important wood for furniture and building materials, due to the high of durability and beautiful color. This study, therefore, aim to investigate the phenol composition, represented by total phenolic,  flavonoid, and flavanol content, as well as antioxidant activity, conducted by DPPH (1, 1-diphenyl-2-picrylhydrazyl) method on Dalbergia latifolia wood. The sample was extracted using ethanol-toluene solvent in a Soxhlet apparat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Fractions 1 and 2 derived from D. latifolia wood showed highest content of total phenolics while fraction 7 and fraction 9 revealed the highest amount of total flavonoid. GC-MS analysis of fraction 1-3 confirmed R-(-) -latifolin from D. latifolia wood [33] . 6), all-E-lutein (7), catechin (8), dalbergin (9), dalbergiphenol (10), dalbin (11), dalbinol (12), dibutyl phthalate (13), ethyl-4-hydroxybenzoate ( 14), eucomic acid (15), isoparvifuran (16), latifolin (17), methyl-4-hydroxybenzoate (18), phenyl β-D-glucopyranoside (19), phthalic acid butyl isobutyl ester (20), p-hydroxybenzaldehyde (21), quercetin ( 22), R-(-)-latifolin (23), stigmasterol (24), β-amyrin acetate, β-amyrin-3-palmitate and 3-acetoxy-oleanoic acid (25) βsitostenone ( 26), β-sitosterol ( 27), extracted from various parts of Dalbergia latifolia [26-28, 33-36, 20-21] .…”
Section: Phytochemical Diversitymentioning
confidence: 85%
See 1 more Smart Citation
“…Fractions 1 and 2 derived from D. latifolia wood showed highest content of total phenolics while fraction 7 and fraction 9 revealed the highest amount of total flavonoid. GC-MS analysis of fraction 1-3 confirmed R-(-) -latifolin from D. latifolia wood [33] . 6), all-E-lutein (7), catechin (8), dalbergin (9), dalbergiphenol (10), dalbin (11), dalbinol (12), dibutyl phthalate (13), ethyl-4-hydroxybenzoate ( 14), eucomic acid (15), isoparvifuran (16), latifolin (17), methyl-4-hydroxybenzoate (18), phenyl β-D-glucopyranoside (19), phthalic acid butyl isobutyl ester (20), p-hydroxybenzaldehyde (21), quercetin ( 22), R-(-)-latifolin (23), stigmasterol (24), β-amyrin acetate, β-amyrin-3-palmitate and 3-acetoxy-oleanoic acid (25) βsitostenone ( 26), β-sitosterol ( 27), extracted from various parts of Dalbergia latifolia [26-28, 33-36, 20-21] .…”
Section: Phytochemical Diversitymentioning
confidence: 85%
“…A study performed on Indonesian medicinal plants revealed that, ethanol extract of D. latifolia leaves exhibited poor antioxidant potential in DPPH assay with 2.6±1.9%of electron donating ability, whereas it performbetter in reducing power assay with 273.2±1.0% of Fe +3 reduction [39] .Methanolic extract of D. latifolia wood showed highest DPPH scavenging activity with IC 50 value of 70±2.55 µg/ml [4] . Among the 12 fractions of D. latifolia wood, fraction 2 showed best DPPH scavenging activity (82.0 and 41.7%) at 500 and 250µg/ml respectively with IC 50 of 303.3 µg/ml [33] . In DPPH, NO and Ferric thiocyanate scavenging activity assay, ethanolic extract of D. latifolia bark exhibited strong antioxidant activity with 92.10±1.10, 86.39±2.12 and 87.22±2.47% of inhibition respectively [14] .…”
Section: Antioxidant Efficacymentioning
confidence: 96%